(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2015)
This paper deals with the analysis of performance bounds of narrowband multiple-input multiple-output (MIMO) fading channels considering the transmission links from the mobile station (MS) to the base station (BS) through non-line-of-sight (NLOS) propagation conditions. It is assumed that an infinite number of local scatterers surround the MS and the BS. The Temporal as well as Spatial correlation properties of channel models are explored along with their capacity. The effect of number of scatterers; Doppler frequency; and isotropic/non-isotropic scattering conditions, on MIMO channel models is investigated in terms of statistical properties of one ring and two ring models, i.e. Time Autocorrelation Function (ACF) and two-dimensional (2D) Space Cross-correlation Function (CCF).Â